Life expectancy following orbital exenteration. Issue 1 (30th May 2014) - Wong, James Chiun Lon; Thampy, Reshma; Cook, Anne
Abstract : Orbital exenteration is a physically debilitating procedure that may be a necessity in the management of orbital malignancy. It requires a sensitive multidisciplinary approach, both preoperatively and postoperatively. Providing life expectancy information for patients during preoperative counselling is pertinent to informed consent and in addressing patients' expectations. A retrospective review from one tertiary care centre was undertaken for a cohort of patients who were exenterated for orbital malignancy between 1998 and 2010. The cases were identified using an International Classification of Diseases 10th Revision (ICD-10)-derived database and were analysed using Prism statistical software (V.5.04). Cause of death was ascertained by liaising with the general practitioner and the National Registrar Office for Births, Deaths, and Marriages, Southport, UK. In total, 41 men and 32 women were identified. Mean age was 72 years with 47 cases living and 26 deceased at the time of review. The overall 5-year survival rate in this study was 64%. Kaplan–Meier analysis for basal cell carcinoma (BCC) against non-BCC returned a p value of 0.0199, with an HR of 0.3927 (CI 0.1788 to 0.8626). Kaplan–Meier analysis for cleared against non-cleared margins returned a p value of 0.2890, with an HR of 0.6571(CI 0.3024 to 1.428). Our results represent the highest 5-year survival data to date. However, the overall prognosis for patients who undergo orbital exenteration for malignancy remains poor. We hypothesise that the causes are multi-factorial. We recommend a multidisciplinary approach to the care of these patients, involving head and neck teams, oncology and other appropriate specialties, to optimise outcomes for this vulnerable patient group.